Zakat Calculator Application: Enhancing the Academic Performance of Islamic Economics Students - Yusuf, Saifudin; Imam Nur Ngaini; Andrean Permadi; Wahidatun Nafiah Al; Hardining Estu M (Open Access Indonesia Journal of Social Sciences, 2025)
Zakat holds profound significance in the Muslim community. Its intricate calculations and diverse categories, however, often pose challenges for individuals striving to fulfill this religious obligation accurately. This research investigates the design, development, and impact of a Zakat Calculator Application on Islamic economics students' academic performance at UNU Blitar. By leveraging technology, this study aims to bridge the gap between traditional learning methods and the evolving needs of students in grasping the complexities of zakat. ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation) guided the application's creation and evaluation. A sample of 60 students from a population of 90 was selected through simple random sampling. Data analysis involved descriptive statistics and an independent two-sample t-test to compare the performance of students using the application with those relying on traditional lecture and discussion methods. The Zakat Calculator Application demonstrated high validity and effectiveness. Expert evaluations yielded excellent scores (media experts: 96.25%, material and strategy experts: 95.55%, curriculum practitioners: 94.69%, lesson plan experts: 92.00%). The t-test results revealed significant improvement in academic performance for students using the application. The experimental group achieved a high academic performance level of 87.5%, compared to 50.5% in the control group. In conclusion, Zakat Calculator Application effectively enhances the academic performance of Islamic economics students. It simplifies zakat calculations, improves understanding of zakat regulations, and promotes compliance with Islamic principles. The application is recommended as a valuable learning tool in Islamic economics education.